Impact of microsatellite status on chemotherapy for colorectal cancer patients with KRAS or BRAF mutation - Huang, Chi-Jung (Oncol Lett, 2016)
KRAS and BRAF mutations are frequently detected in cases of colorectal cancer (CRC). The microsatellite status of patients with CRC and mutated KRAS/BRAF is important when determining cancer therapy. In the present study, the microsatellite status and genetic polymorphisms of KRAS (codons 12 and 13) and BRAF (V600E) were characterized in CRC tissue. The mismatch repair activity and oncogenic potential of KRAS were assessed by immunoblots from two KRAS-mutated CRC cell lines, SW480 and HCT116, with different microsatellite statuses, following treatment with 5-fluorouracil (5-FU) and oxaliplatin. Of all the 205 patients with CRC enrolled in the present study, 31.2% (64 of 205) had a KRAS or BRAF mutation, and 79.7% (51 of 64) of these patients with a KRAS/BRAF mutation exhibited microsatellite stability (MSS), indicating that microsatellite status is correlated with KRAS/BRAF mutation (P=0.027). A higher proportion (39.0%, 41 of 105) of elderly patients (≥62.6 years) had mutated KRAS or BRAF than younger patients (<62.6 years; 23.0%, 23 of 100; P=0.013). In the subgroup of 154 patients with MSS, patients without the KRAS or BRAF mutation (n=110) had longer disease-specific survival rates (58.8±9.4%) than patients with KRAS or BRAF mutations (n=44; 50.6±11.0%; P=0.043). Cytoplasmic KRAS levels decreased whereas nuclear MutS protein homolog 2 (MSH2) levels increased slightly in CRC HCT116 cells that were microsatellite instable, following treatment with 76.9 µM 5-FU for 2 days. In microsatellite stable SW480 cells, MSH2 levels markedly increased in the nucleus following 150 µM oxaliplatin treatment for 3 days. However, no significant change was observed regarding KRAS distribution in these cells. The results of the present study suggest that it is important to identify patients with CRC who may benefit from adjuvant chemotherapy with 5-FU or oxaliplatin, particularly CRC patients with MSS and mutated KRAS or BRAF, who have poorer overall survival rates than patients with microsatellite instability. Knowledge of the microsatellite status of patients and whether they harbor KRAS or BRAF mutations may enable more effective therapeutic strategies to be developed. Further prospective studies are required to validate the findings of the current study.